The impacts of natural flood management approaches on in-channel sediment quality - Janes, Victoria J.; Grabowski, Robert C.; Mant, J.; Allen, D.; Morse, J. L.; Haynes, H. (Wiley, 2016)
Natural Flood Management (NFM) techniques aim to reduce downstream flooding by storing and slowing the flow of stormwater to river channels. These techniques include a range of measures, including setback stormwater outfalls and the physical restoration of channels and floodplains, to improve the natural functioning of catchments. An additional benefit of NFM measures is the potential reduction in sediment and pollutant delivery to the channel. Urban development releases a variety of heavy metal and nutrient pollutants that enter rivers through stormwater outfalls with adverse effects on the aquatic ecosystem. In this study, the influence of channel modification and quality of the river habitat on the sediment quality surrounding stormwater outfalls was assessed. Sediment samples were taken at several outfalls within the Johnson Creek catchment, Oregon, USA, and analysed for a variety of urban pollutants. The level of river habitat quality and modification at each site were assessed using a semi-quantitative scoring methodology. Significant increases in pollutant levels were observed at outfalls, with a greater and more variable increase at direct compared to setback outfalls. Removal efficiency of certain pollutants was found to be significantly correlated to the level of habitat quality or modification (for Fe, Ba, Sn, Mg, P, K) indicating that more natural reaches had greater potential for pollutant removal. The findings highlight the multiple benefits associated with NFM and river restoration approaches in relation to sediment quality and pollutant content.
Keywords: restoration; outfall; setback outfall; sediment; River Habitat Survey; pollutant; Natural Flood Management